Improvement of Blood Flow and Epidermal Temperature in Cold Feet Using Far-Infrared Rays Emitted from Loess Balls Manufactured by Low-Temperature Wet Drying Method: A Randomized Trial - Yong Il Shin; Min Seok Kim; Yeong Ae Yang; Yun Jeong Lee; Gye Rok Jeon; Jae Ho Kim; Yeon Jin Choi; Woo Cheol Choi; Jae Hyung Kim (Biomedicines)
Background: Cold feet syndrome is characterized by hypersensitivity of sympathetic nerves to cold stimuli, resulting in vasoconstriction and reduced peripheral blood flow. This condition causes an intense cold sensation, particularly in the extremities. Although hormonal changes (e.g., during childbirth or menopause) and psychological stress have been implicated, the mechanisms and effective treatments remain unclear. Methods: Ninety adult volunteers were randomized into three groups based on the type of heating mat applied to the feet, with surface temperatures gradually increased from 20 °C to 50 °C. Group A (control) used non-FIR electric mats, Group B used carbon FIR mats, and Group C used loess bio-ball FIR mats. Blood flow (mL/min/100 g) and epidermal temperature (°C) in the left big toe (LBT) and right big toe (RBT) were measured before and after heating or FIR exposure using laser Doppler flowmetry and infrared thermometers. Results: No significant changes in blood flow or skin temperature were observed in Group A. In Group B, blood flow increased by 15.07 mL/min/100 g in the LBT (from 4.12 ± 2.22 to 19.19 ± 5.44) and by 14.55 mL/min/100 g in the RBT (from 4.26 ± 2.29 to 18.81 ± 4.29). In Group C, blood flow increased by 32.86 mL/min/100 g in the LBT (from 4.23 ± 1.64 to 37.09 ± 6.04) and by 32.63 mL/min/100 g in the RBT (from 4.20 ± 1.61 to 36.83 ± 6.48). Epidermal temperature also increased significantly in Group C. All changes in Groups B and C were statistically significant (p < 0.05), with Group C showing the most prominent enhancement. Conclusions: The loess bio-ball mat significantly increased both peripheral blood flow and epidermal temperature compared to the electric and carbon mats. These findings suggest that FIR emitted from loess bio-balls may enhance peripheral circulation through hypothalamus thermogenic response and nitric oxide (NO)-dependent pathways and could serve as a complementary and non-invasive intervention for individuals with poor blood flow.